A curriculum framework for lifelong learning of emerging Nigerian farmers in financial farm management - Oluwumi, Oluwadamilola Oluwatemilorun (Stellenbosch : Stellenbosch University, 2025)
Oluwumi, O. O. 2025. A curriculum framework for lifelong learning of emerging Nigerian farmers in financial farm management. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/a944b986-9c27-4e1b-90c5-d5f29ab260c9